1974
DOI: 10.1177/22.7.697
|View full text |Cite
|
Sign up to set email alerts
|

Automated Classification of Normal and Abnormal Leukocytes

Abstract: The development of an automated system for counting and classifying normal and abnormal leukocytes in peripheral blood smears is described. General requirements are discussed and the results of a simulation experiment are presented. A sample of 1572 leukocytes, divided equally among 17 types, was photographed and analyzed using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Bacus [28], Green [29], Kruse [30], and Zack [31] have shown that a sampling density of about 0.5 p is necessary and sufficient for the analysis of erythrocyte morphology. Bacus [32], Young [33], [34], Brenner [35], Prewitt [19], Ingram [36], and Tyko [37] have also seemed to confirm this figure for leukocyte analysis. In the analysis of exfoliative cervical cytology Bartels [38] has shown through careful studies that 0.5 p sampling is necessary for accurate cell classification.…”
Section: Reinventing the Microscopementioning
confidence: 66%
“…Bacus [28], Green [29], Kruse [30], and Zack [31] have shown that a sampling density of about 0.5 p is necessary and sufficient for the analysis of erythrocyte morphology. Bacus [32], Young [33], [34], Brenner [35], Prewitt [19], Ingram [36], and Tyko [37] have also seemed to confirm this figure for leukocyte analysis. In the analysis of exfoliative cervical cytology Bartels [38] has shown through careful studies that 0.5 p sampling is necessary for accurate cell classification.…”
Section: Reinventing the Microscopementioning
confidence: 66%
“…The percentages of correct classification calculated from these reports are 92.6% (Hematrak) and 95.9% (LARC). In a laboratory experiment on WBC differentiation (Brenner et a/. 1974) a correct classification was obtained in 96.8';/,.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such considerations may be seen in the presentation of results in a system for the classification of immature white blood cells [7]. There, the "extended diagonal" expresses in a crude manner the fact that the assignment to a neighboring class (e.g., assigning a myelocyte to the class of metamyelocytes) is not regarded as a severe error.…”
Section: Possible Future Developmentsmentioning
confidence: 99%